2007
DOI: 10.1093/nar/gkl1164
|View full text |Cite
|
Sign up to set email alerts
|

Deinococcus glutaminyl-tRNA synthetase is a chimer between proteins from an ancient and the modern pathways of aminoacyl-tRNA formation

Abstract: Glutaminyl-tRNA synthetase from Deinococcus radiodurans possesses a C-terminal extension of 215 residues appending the anticodon-binding domain. This domain constitutes a paralog of the Yqey protein present in various organisms and part of it is present in the C-terminal end of the GatB subunit of GatCAB, a partner of the indirect pathway of Gln-tRNAGln formation. To analyze the peculiarities of the structure–function relationship of this GlnRS related to the Yqey domain, a structure of the protein was solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 49 publications
2
40
0
1
Order By: Relevance
“…42 A YqeY domain appended to the C-terminus of the Deinococcus radiodurans GlnRS is important for the enzyme to productively bind to tRNA Gln . 42 The tail domains in the AdT subunits play a similar role by enabling specific binding to their tRNA substrates. 21,22 Because YqeY is homologous to but more distantly related to GatB and GatE than they are to each other, it serves as an ideal outgroup for the tail domain phylogeny.…”
Section: Ancient Divergence Between Gatb and Gatementioning
confidence: 99%
“…42 A YqeY domain appended to the C-terminus of the Deinococcus radiodurans GlnRS is important for the enzyme to productively bind to tRNA Gln . 42 The tail domains in the AdT subunits play a similar role by enabling specific binding to their tRNA substrates. 21,22 Because YqeY is homologous to but more distantly related to GatB and GatE than they are to each other, it serves as an ideal outgroup for the tail domain phylogeny.…”
Section: Ancient Divergence Between Gatb and Gatementioning
confidence: 99%
“…These recognition complexes effect the transfer of activated amino acids to the correct tRNA molecule, producing aminoacyl-tRNAs needed for protein synthesis by the ribosome. Errors in charging are rare (3,4), and it is generally agreed that the low frequency of mischarging is based on synthetase recognition of specific identity elements in tRNA molecules (5). Many investigators (6)(7)(8) have observed that the codon table tends to reduce deleterious effects of point mutations (9) by assuring that they do minimal violence to the physical requirements of protein folding.…”
mentioning
confidence: 99%
“…A similar model has recently been proposed for a natural chimeric synthetase, the Deinococcus GlnRS. 26 This enzyme contains a unique C-terminal extension, which is a paralog of the Yqey proteins and increases the affinity of the enzyme for its cognate tRNA. As the TRBD present in aminoacyl-tRNA synthetases and non-catalytic proteins, Yqey proteins exist either in free form or as appendices to GlnRSs and the tRNA-binding subunits of bacterial and archaeal amidotransferases.…”
Section: Discussionmentioning
confidence: 99%